Improving care collaboration for NICU patients to decrease length of stay and readmission rate. Issue 2 (21st October 2017) - Welch, Cherrie D; Check, Jennifer; O'Shea, T Michael
Abstract : Background: Medically complex patients in neonatal intensive care units (NICUs) typically require long hospitalisations and care from multiple subspecialists. Scheduled multidisciplinary discussions could improve collaboration and continuity of care and thereby improve patient outcomes. The specific aims of the project were to decrease the average length of hospitalisation by at least 1 day and improve parent satisfaction ratings on a standard questionnaire by the end of our project's first year, and to maintain a stable (or decreased) cause-related (30-day) readmission rate. Methods: We designed a quality improvement project to enhance collaboration and continuity of care for medically complex infants cared for in the NICU of Brenner Children's Hospital. Weekly multidisciplinary team meetings were held to discuss the long-term plan for patients who met specific criteria. Attendees included attending neonatologists, paediatric surgeons, a physical therapist, an occupational therapist, a speech therapist, a social worker, a nurse coordinator for palliative care, a family support coordinator, the NICU Nurse Manager, a hospital chaplain, mid-level providers, bedside nurses, a nurse quality improvement leader and the leaders and database manager for the quality improvement project. When needed for specific patients, a bioethicist was included. Results: One year after implementing the project, the average duration of hospitalisation had decreased by 6.5 days. Cause-related readmission rates decreased from 3.33% to 0.95%. Parent satisfaction scores did not change significantly. Conclusions: Weekly multidisciplinary meetings to coordinate and provide continuity of care for medically complex neonates in our NICU was associated with improved patient outcomes.